Developing and exploiting linguistic resources in research and in the didactics of Specialised Translation - SARIDAKIS, IOANNIS E. (International Journal of Language, Translation and Intercultural Communication, 2016)
This paper outlines the main state-of-the-art linguistic resources that can be developed and used in the research and in the didactics of Specialised Translation. In addition, it points to the still largely unexplored potential from the combination of Corpus Linguistics, Descriptive Translation Studies and Systemic Functional Linguistics into a single scientific and research agenda, to the benefit of both translation practitioners and trainee translators.